Five new records and an annotated checklist of the leeches (Annelida: Hirudinida) of Iran - Darabi-Darestani, Kaveh; Sari, Alireza; Sarafrazi, Alimorad (Zootaxa, 2016)
The present checklist contains 22 species belonging to 14 genera of six families of leeches known to date from Iran. Five species including Dina punctata punctata Johannson, 1927, Erpobdella monostriata (Lindenfeld & Pietruszynski, 1890), E. vilnensis (Liskiewicz, 1925), Trocheta haskonis Grosser, 2000 and Glossiphonia concolor (Apathty, 1888) are new records for the country.